Description of the larva and pupa of Neocorvicoana reticulata (Kirby, 1819) (Coleoptera: Scarabaeidae: Cetoniinae: Gymnetini) - Ibarra-Polesel, Mario G.; Neita-Moreno, Jhon C.; Larrea, Dario D.; Damborsky, Miryam P. (Zootaxa, 2017)
The third instar and pupa of Neocorvicoana reticulata (Kirby, 1819) (Coleoptera: Scarabaeidae: Cetoniinae: Gymnetini) from Argentina, are described and illustrated. This is the first description of immatures in this genus. A key to the known third-stage larvae of New World Gymnetini species is provided, which now includes 19 species in 10 genera.